THE INFLUENCE OF LOCAL GOVERNMENT CHARACTERISTICS ON REGIONAL FINANCIAL PERFORMANCE ACEH PROVINCE - Nadira Salsabila; M Rasyidin; M Saleh (CV. Radja Publika, 2025)
This study aims to examine the Influence of Regional Government Characteristics on the Financial Performance of Aceh Province. The characteristics of the regional government studied include the size of the region, the level of dependence on the center and regional financial performance examined using the Harmony Ratio which includes operating expenses, capital expenditures and regional expenditures. The research method used is quantitative. This study uses secondary data using time series data for 30 years from 1994 to 2023. The data used in this study are annual data from each variable sourced from the official website (BPS and PPID). Data analysis uses multiple linear regression analysis. The results of this study state that regional size does not affect regional financial performance as measured using the harmony ratio, namely operating expenses, capital expenditures and regional expenditures. While the variable Level of dependence on the center has a positive and significant effect on regional financial performance as measured using the harmony ratio, namely operating expenses, capital expenditures and regional expenditures in Aceh Province.